Reassessing the importance of 'lost pleasure' associated with smoking cessation: implications for social welfare and policy. Issue Volume 27:Issue e2(2018) (28th November 2017) - Pechacek, Terry Frank; Nayak, Pratibha; Slovic, Paul; Weaver, Scott R; Huang, Jidong; Eriksen, Michael P
Abstract : Introduction: Benefit–cost analyses of tobacco regulations include estimates of the informed choice of smokers to continue smoking. Few studies have focused on subjective feelings associated with continued smoking. This study estimates how smoker discontent and regret relate to risk perceptions and health concerns. Methods: We analysed data from a 2015 nationally representative, online survey of 1284 US adult current smokers. Information was collected on regret, intention to quit, perceived addiction, risk perceptions and health concerns. Multivariate logistic regression adjusting for sociodemographics and health status was used to examine factors associated with smoker discontent. Results: More than 80% of current smokers report high (22.5%) or very high (59.8%) discontent due to inability to quit, perceived addiction and regret about having started to smoke. Higher levels of discontent did not vary significantly by sex, age, race/ethnicity, education or income (adjusted odds ratios (AORs) 0.5–1.2). Compared with the smokers expressing low (5.9%) or very low (3.6%) discontent, those expressing higher levels of discontent perceived their health status as fair/poor (AOR=2.3), worried most of the time about lung cancer (AOR=4.6) and felt they were more likely to develop lung cancer in the future (AOR=5.1). Conclusion: The proportion of smokers who might be characterised as having a preference to continue smoking are greatly outnumbered by addicted, discontent and concerned smokers who want to quit and regret ever having started to smoke. These discontent smokers could have a substantial net welfare gain if new regulations helped them escape their concerns about the health effects from continuing smoking.